Undergraduate Economics Students’ Opinion about Research Supervisors: The Ghanaian Public University Context - Owusu, Anthony Akwesi (Advances in Social Sciences Research Journal, 2018)
Supervisor-student relationship is crucial for completion of an undergraduate programme since students, as a requirement to complete, are expected to write a project work. The purpose of this study was to find economics students’ views about their supervisors. Using a cross-sectional descriptive design, 148 economics major trainee teachers from two faculties in a public university were randomly selected. The study showed that students had opinions that supervisors are guides who must show interest in students’ research. Again, students’ opinion was that they did not have adequate guidance and mentoring from supervisors and this contributed to their negative perceptions relative to their relationship with supervisors. Also, gender was found to have an association with students’ perception about relationship with supervisors. The study advocated for measures to be put in place to mitigate the negative effects of student-supervisor rift which has detrimental effects on student completion rates among students in Ghana.